Development of Statistical Literacy Questions for Prospective Mathematics Teachers - Rahma Siska Utari; Zulkardi Zulkardi; Ratu Ilma Indra Putri; Ely Susanti (Jurnal Inovasi Matematika, 2023)
Statistical literacy was one of the important abilities that must be possessed by prospective mathematics teachers in the era of society 5.0. This research was qualitative descriptive to develop statistical literacy questions for prospective mathematics teachers using indicators of the five bases of statistical literacy and PMRI principles. The questions were developed using a design research type of development study to see the validity and practicality of the questions. The research stages included the preliminary stage, and the prototyping stage (self-evaluation, expert review, one-to-one, and small group). As many as 13 prospective mathematics teachers participated in this study, in the one-to-one stage and the small group stage. Data were collected through walkthroughs, observations, interviews, and video recordings. Data were analyzed qualitatively to describe the results of each stage. The results showed that the statistical literacy questions developed were valid and practical. Validity was shown from the expert review stage which validates the content, construct and language aspects used in the questions. Practicality can be seen from the one-to-one and small group stages where students can work on the questions given. Further research was needed using more subjects to see the potential effects that emerge from this study.